Overview of Transporters in Pharmacokinetics and Drug Discovery. Issue 1 (31st August 2018) - Zhang, Yan
Abstract: Transporters play important roles in absorption, distribution, metabolism, and elimination (ADME) processes, as well as drug pharmacokinetics (PK) and pharmacodynamics (PD). They are also important in maintaining the homeostasis of endogenous compounds and nutrients in the body. Increasing evidences also suggest that they are important in mediating drug‐drug interactions (DDIs). While the significance of transporters in drug pharmacodynamics and DDIs are beyond the scope of this overview, the basic concepts of transporters, their contributions in membrane permeation processes, and their roles in influencing drug ADME pathway and PK will be discussed. © 2018 by John Wiley & Sons, Inc.